2020
DOI: 10.14814/phy2.14533
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal transformations for gaze control

Abstract: Sensorimotor transformations require spatiotemporal coordination of signals, that is, through both time and space. For example, the gaze control system employs signals that are time‐locked to various sensorimotor events, but the spatial content of these signals is difficult to assess during ordinary gaze shifts. In this review, we describe the various models and methods that have been devised to test this question, and their limitations. We then describe a new method that can (a) simultaneously test between al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 227 publications
(382 reference statements)
2
28
0
Order By: Relevance
“…Previous reports on FEF responses from our lab have reported that responses do not fit exactly against spatial models like Te or Ge, but actually may fit best against intermediate models between the canonical ones (Fig. 4A, lower left) (Sajad et al, 2020). As in our previous studies (Sadeh et al, 2020;Sajad et al, 2016), we found that a T-G continuum (specifically, steps along the 'error line' between Te to Ge) best quantified the SEF egocentric transformation (Fig.…”
Section: Intermediate Spatial Models Used In Main Analysissupporting
confidence: 71%
See 2 more Smart Citations
“…Previous reports on FEF responses from our lab have reported that responses do not fit exactly against spatial models like Te or Ge, but actually may fit best against intermediate models between the canonical ones (Fig. 4A, lower left) (Sajad et al, 2020). As in our previous studies (Sadeh et al, 2020;Sajad et al, 2016), we found that a T-G continuum (specifically, steps along the 'error line' between Te to Ge) best quantified the SEF egocentric transformation (Fig.…”
Section: Intermediate Spatial Models Used In Main Analysissupporting
confidence: 71%
“…Note that in the current study, deviations of gaze from the target (used to fit response fields against G) were produced in part by the landmark shift. However, this alone does not likely explain the T-G transition in our cells, because it happened continuously through the task, it was spatially separable and often uncorrelated with the neural response to the landmark shift (discussed below), and much of the gaze errors used to calculate this transition were not due to the landmark shift, but appeared to be due to general internal 'noise', as in our previous studies (Sadeh et al, 2020;Sajad et al, 2020Sajad et al, , 2016 which was even larger without a landmark (Li et al, 2017). In short, the landmark shift clearly contributed to gaze errors, but cannot alone explain the T-G transition we observed here in SEF cells.…”
Section: Egocentric Transformations In the Gaze Systemmentioning
confidence: 75%
See 1 more Smart Citation
“…This occurs when the ideal coordinate frame is not used for the plot (Fig. 3b), but even for the best model, some variability (residuals) persists due to non-spatial factors such as attention and motivation 6,7,33,34 . For the first step in our new analysis, we separated and plotted the response fields for each of the four target-landmark configurations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Saccade generation involves multiple transformations of reference frames in neurons (Crawford and Guitton 1997;Goossens and van Opstal 2012;Leigh et al 1997;Sajad et al 2020). For example, visual targets for saccades are represented by retinocentric sensory maps, and gaze shift commands are initially also specified as desired displacement vectors in retinocentric coordinates (Goldberg and Bruce 1990;Hepp et al 1993; Moschovakis and Highstein 1994;Robinson 1972;Schiller and Stryker 1972;Schlag-Rey et al 1989;van Opstal et al 1991).…”
Section: Introductionmentioning
confidence: 99%